Direct democracy worldwide - Altman, David (Cambridge University Press, 2011)
"Challenging the assumption that models of direct democracy and representative democracy are necessarily at odds, this book demonstrates how practices of direct and representative democracy interact under different institutional settings and uncovers the conditions that allow them to coexist in a mutually reinforcing manner"--